Block's disinfection, sterilization, and preservation - McDonnell, Gerald E.; Hansen, Joyce M. (Wolters Kluwer, 2021)
"Infection control and concerns about spread of disease date back to ancient times: early Greek, Roman, and Biblical texts outline strict dietary guidelines, quarantines for people with leprosy, and instructions for returning soldiers to burn equipment and clothes. Aristotle instructed Alexander the Great to require his armies to boil their drinking water. Today, concerns about drug resistance (eg: farmed fish as a source of antibiotic resistance; drug-resistant tuberculosis; drug-resistant bacteria on endoscopes) dominate news headlines and command serious research and industry investment.Seymour S Block's Disinfection, Sterilization, and Preservation was first published in 1968, and is considered to be the gold standard for those involved with technologies or products dependent on preservatives, sterilization or disinfection. The various sections and detailed chapters of the book include introductions, fundamental principles of activity, chemical types of disinfectants/sterilants, controls of particular types of microorganisms, physical disinfection/sterilization technologies, medical & health related applications, test methodologies, and miscellaneous other topics. The last edition was published in 2000, and since that time much has changed in our understanding of the risks, the technologies available, and the regulatory environments in the practical applications of these technologies. Additionally, focus has somewhat shifted from "how to kill it" to "how to prevent it" A new edition, discussing new understandings of microbes and how to manage them through disinfection and prevention is necessary. Dr. Block has passed away, but he has several colleagues and previous contributors who are desirous of carrying the mantle of this important title. The proposed editors are well respected in the area, with backgrounds in the antimicrobial control of infection risks; one of the editors has a greater background in the medical application of technologies and the other for industrial applications, offering a nice balance"--